The role of continuous review in achieving the quality of the financial statements information: (Field study on external auditing offices - Khartoum State) - د. زين العابدين إبراهيم يوسف,; د الأمين محمود عبد المجيد حسن, (White Nile Journal for Studies and Research, 2021)
The study aimed to demonstrate the role of continuous review in achieving the quality of financial statement information. The problem of the study was that the financial statements are not reviewed periodically and regularly, which made the financial statements information unreliable by the users of these lists. The study followed the historical approach, deductive approach, inductive approach and descriptive analytical approach. The study reached the following results: The continuous audit procedures helped the auditor to express a neutral technical opinion regarding the veracity of the financial statements information. The continuous review helped to detect errors as soon as they statement information. occurred and correct them, which led to achieving the quality of the financial statements information. The continuous audit procedures resulted in increased confidence in the financial statements information. The study also recommended a number of recommendations, including: the necessity of proper planning of work and supervision of the collection of actual evidence that works to achieve the quality of financial {Keywords: Continuous review, Quality of information, Financial statements